2017
DOI: 10.1097/brs.0000000000001883
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch Between Proximal Rod Contouring and Proximal Junctional Angle

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…Both over- and undercorrection of SVA and PI-LL mismatch have been proposed as potential risk factors leading to the development of PJK. Yan et al 13 have suggested that in patients who undergo extensive corrective surgery with sagittal overcorrection, postoperative alignment might not be sustainable, as the body tends to balance itself. For instance, they proposed that patients with an overcorrected sagittal profile would unconsciously generate compensatory mechanisms to realign and correct sagittal balance, commonly via the unfused segments and pelvic compensation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both over- and undercorrection of SVA and PI-LL mismatch have been proposed as potential risk factors leading to the development of PJK. Yan et al 13 have suggested that in patients who undergo extensive corrective surgery with sagittal overcorrection, postoperative alignment might not be sustainable, as the body tends to balance itself. For instance, they proposed that patients with an overcorrected sagittal profile would unconsciously generate compensatory mechanisms to realign and correct sagittal balance, commonly via the unfused segments and pelvic compensation.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, they proposed that patients with an overcorrected sagittal profile would unconsciously generate compensatory mechanisms to realign and correct sagittal balance, commonly via the unfused segments and pelvic compensation. 13 Additionally, in patients who undergo aggressive correction, the development of PJK may be influenced by surgical technique. Mauro et al 10 predicted that when rod cantilever techniques with multiple Smith-Peterson osteotomies were used, this could lead to significant stresses at the proximal adjacent disc and vertebrae, which may lead to PJK.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6,13,14] In addition, it was recently shown that two interesting parameters representing the spine's sagittal alignment at the proximal part of the instrumentation, namely the rod contouring angle (RCA) and its mismatch with the proximal junctional angle (PJA), are associated with the occurrence of PJK. [15,16] Decreased RCA, representing the amount of kyphotic curvature bent into the rod, has been suggested to be a risk factor for PJK, but the importance of a mismatch between PJA and RCA (PJA-RCA) has not been fully understood and has rarely been studied in AIS. [15] Furthermore, spinous processes are often sacrificed during posterior surgery harvesting cancellous bony material for spondylodesis.…”
Section: Introductionmentioning
confidence: 99%
“…2,4,5 There are surgical, radiographic, and patient-specific risk factors that may lead to the development of PJK. 2,3,[6][7][8][9][10] Fracture at the upper instrumented vertebrae is the most common mechanism for the development of PJK. 2,7 Proximal junction failure (PJF) generally refers to radiographic findings of PJK coupled with adverse clinical symptoms that can include increasing pain, functional impairment, and even neurologic deficits in severe cases.…”
Section: Introductionmentioning
confidence: 99%